Safety and technological application of autochthonous Streptococcus thermophilus cultures in the buffalo Mozzarella cheese - Silva, Luana Faria [UNESP]; Sunakozawa, Tássila Nakata [UNESP]; Amaral, Daniel Mathias F. [UNESP]; Casella, Tiago; Nogueira, Mara Correa Lelles; De Dea Lindner, Juliano; Bottari, Benedetta; Gatti, Monica; Penna, Ana Lúcia Barretto [UNESP] (Elsevier, 2020)
Thermophilic and mesophilic lactic acid bacteria (LAB), such as Streptococcus thermophilus, Lactobacillus delbrueckii subsp. bulgaricus, Lactobacillus helveticus, and Lactococcus lactis, play a crucial role in the technological and sensory quality of Mozzarella cheese. In this study, the safety (genes encoding virulence factors and antibiotic resistance) and acidifying activity of autochthonous S. thermophilus cultures were evaluated in order to choose the most suitable strain for industrial application. The safe and good acidifying culture was tested in two buffalo Mozzarella cheese batches: Mozzarella cheeses produced with autochthonous culture (SJRP107) and commercial culture (STM5). The cultivable LAB was evaluated by culture-dependent method (plate counting) and the quantification of S. thermophilus cultures (commercial and autochthonous) were evaluated by culture-independent method RealT-qPCR (real-time quantitative polymerase chain reaction). The texture, physicochemical and proteolytic properties of the Mozzarella cheeses were similar for both batches. The nonstarter LAB count was higher during manufacture than in the storage, and the RealT-qPCR indicated the presence of S. thermophilus culture until the end of storage. S. thermophilus SJRP107 presented high potential for safety application in the production of Mozzarella cheese. Furthermore, considering the culture characteristics and their relationship with product quality, further studies could be helpful to determine their effect on the sensory characteristics of the cheese.
Keywords: Cultivable cells; Lactic acid bacteria; Quantitative real time PCR; Safety; Technological application